Risk of contamination of phreatic aquifer with pesticides in the basin of Ludueña stream, Argentina - Montico, Sergio; Di Leo, Néstor Cristian (Ecosistemas y Recursos Agropecuarios, 2021)
The objective of this work was to evaluate the risk of contamination of phreatic aquifer by the use of pesticides in the main crops within the basinof the Ludueña stream, Santa Fe, Argentina. Thirteen cartographic units (CU)formed by five soil series were evaluated. Use strategies for the fourteen most usedpesticides in main crops in the basin were investigated. Attenuation Factor (AF) and Retardation Factor (RF) of the pesticides in the series and CU were calculated by applying Integration of Environmental Risk Indices (IERI). The results of RFby mobility and AF were classified by the probability of leaching. The average net water recharge value used for the calculation of AF was 1.2 mm d?1, andgeoreferenced maps were constructed for each most mobile herbicide, insecticide and fungicide in the C horizon of the CUs. No clear trend was found in the mobility of pesticides in A, B and C horizons of the five soil series. Herbicides were more mobile than insecticides and fungicides. Regarding the AF, it was lower in the C horizon increasing the risk of phreatic aquifer contamination, and no clear difference was observed between the horizons A and B. Different risks of pesticide leaching were determined in the different environments of the basin. The applied index that considers the retardation and attenuation of the pesticide dynamics was useful to evaluate these risks.